PENGARUH PENERAPAN STRATEGI PELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE (ETH) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PANCUNG SOAL - Rahmil, Rahmil; Zulfaneti, Zulfaneti; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
This research is based on the background by the studentâsÂ understanding mathematical concept is low, which cause the result of learning student mathematics is not good. This research aim to 1) know whether studentâs understanding of mathematical concept Â student with implementing active study strategy Â type of Everyone Is A Teacher here better than the understanding of mathematical concept by applying with conventional teaching Â class of VIII SMPN 1 Pancung Soal 2013 / 2014 school year.Â 2). Howâs student motivation to learn mathematics.This type of research is experimental. Population in this research is all student in grade VIII SMPN 1 Pancung Soal Â 2013 / 2014 school year, which consist of 6 class. Tehcnique of random sampling is the chosen class VIII.2 as experimental class and Â VIII.3 as control class. Research InstrumentÂ areÂ enquette form and the final test. Test Â used is essai with the reliabilitation Â 0,91. Technique analyse data which is use test of t one side with MINITAB.Based on final data test analysis can be obtained by p-Value = 0,041 smaller than a = 0,05. This means can be concluded students Â understanding of mathematical concept by implementing active study strategy Â type of Everyone Is A Teacher Here better than the students understanding of mathematical concept by applying convetional learning in class of VIII SMPN 1 Pancung Soal 2013 / 2014, school year. Pursuant to enquette analysis motivate students to learn by using active strategy type of Everyone Is A Teacher Here is motivating.Â